The Jurnal Ilmiah Pekerjaan Sosial Vol.xx No.xx Tahun 20xx: PENGEMBANGAN MODAL SOSIAL PADA ORGANISASI BANK SAMPAH AVATAR DALAM MENANGANI KEMISKINAN MELALUI AGILE SOCIAL CAPITAL DEVELOPMENT MODEL - Irma Dewi Istikomah; Marjuki Marjuki; Suharma Suharma (Politeknik Kesejahteraan Sosial Bandung, 2023)
Social capital is currently widely used by academics and social practitioners in various studies, especially as an alternative to other forms of modality such as economic capital, cultural capital, and human capital. So it is not uncommon if social capital is also converted into an asset owned by a group of organizations, or the community. The utilization of social capital in the organization is very useful in determining the direction of movement, structure, and organizational culture. The Avatar Waste Bank organization, which is located in Binangun Village, Bantarsari District, Cilacap Regency, Central Java Province, was chosen as the study organization in social capital development through a model, the Agile Social Capital Development Model. The agile Social Capital Development Model is a model developed in the form of applying the four values ​​and twelve Agile principles in every activity and organization activity. This model is adapted from the Agile Manifesto concept which is commonly used in the world of software development. The application of the Agile Social Capital Development Model in organizational activities is expected to help develop social capital at the Avatar Waste Bank to become an agile and flexible organization in every condition, especially in dealing with poverty.